1992
DOI: 10.1111/j.1751-1097.1992.tb04218.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Measures of Photosystem Ii Electron Transfer Inhibition in Anthraquinone‐treated Chloroplasts

Abstract: We have previously used chlorophyll fluorescence measurements at Fmax conditions (i.e. with Photosystem II electron acceptor QA reduced) to monitor the action of 9,10-anthraquinones on photosynthetic electron transport in plant chloroplasts. The present investigation employs two additional techniques to characterize the extent of electron transport inhibition induced by the addition of substituted anthraquinones to the suspending medium of spinach chloroplasts. Results are presented for spectrophotometric assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…2-Heptyl-8-hydroxyquinoline-N-oxide is known to block electron transfer in many bacterial respirations, including sulfate respiration (9). A 50 M concentration of 2-heptyl-8hydroxyquinoline-N-oxide was shown to reduce fumarate-dependent hydrogen uptake by French press vesicles from 700 to 0 nmol of H 2 per min per mg.…”
Section: Resultsmentioning
confidence: 99%
“…2-Heptyl-8-hydroxyquinoline-N-oxide is known to block electron transfer in many bacterial respirations, including sulfate respiration (9). A 50 M concentration of 2-heptyl-8hydroxyquinoline-N-oxide was shown to reduce fumarate-dependent hydrogen uptake by French press vesicles from 700 to 0 nmol of H 2 per min per mg.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, extra information, such as the function describing the dependence of chromophore concentration on ligand concentration, is necessary to obtain a unique solution. On the other hand, a trilinear model usually requires no extra information to provide a unique solution. , A number of applications of trilinear models in spectroscopic studies have been reported. , …”
Section: Introductionmentioning
confidence: 99%
“…14,18 A number of applications of trilinear models in spectroscopic studies have been reported. 8,[19][20][21][22][23][24][25][26][27][28][29] We compare our experimental spectroscopic results with properties calculated using semiempirical molecular orbital methods. Linear multiple regression is used to analyze different effects on spectral shifts.…”
Section: Introductionmentioning
confidence: 99%
“…Once the process of electron transfer was triggered by actinic light, the level of the fluorescence induced by the modulated analytical light is directly dependent on the QA redox state. The modulated signal measured through the lock-in amplifier is, therefore, proportional to the fluorescence kinetic induced by the actinic light (16,17).…”
Section: Methodsmentioning
confidence: 99%